Assessment of trade-off balance of maize stover use for bioenergy and soil erosion mitigation in Western Kenya - Jindo, Keiji; Ghaffari, Golaleh; Lamichhane, Manisha; Lazarus, Asher; Sawada, Yoshito; Langeveld, Hans (Frontiers in Sustainable Food Systems, 2025)
IntroductionKakamega Forest, Kenya's last tropical rainforest, faces threats from escalating demands for firewood, charcoal, and agricultural expansion driven by population growth. Sustainable resource management is critical, with maize stover—a common lignocellulosic crop residue—proposed as a source for biogas and bioslurry production. However, its removal raises concerns about soil fertility and erosion control. This study evaluates the trade-off between maize stover's use for energy generation and its role in soil erosion mitigation in Western Kenya, considering biophysical conditions and households' socio-economic status.MethodsSocio-economic data were collected from 91 households to assess energy usage. Soil erosion was quantified using the Revised Universal Soil Loss Equation (RUSLE). High-resolution remote sensing, self-organizing maps (SOM), and Hidden Markov Models (HMM) were integrated for annual field condition monitoring. A decision-tree machine learning model identified farm characteristics favorable for maize stover use in biogas production.ResultsLarger households were found to consume more energy per capita, while proximity to forests did not significantly influence firewood or charcoal consumption. Maize yields were significantly associated with land preparation methods (tractor, oxcart, or manual plowing; p < 0.001) and field size (p < 0.05). Remote-sensing data indicated that the distance between homesteads and fields impacted crop growth status. RUSLE analysis revealed that soil erosion was more strongly influenced by landscape features than by soil properties or farming practices.DiscussionThe integration of SOM-HMM and microsatellite data improved field monitoring and data accuracy, providing valuable insights for sustainable agricultural practices in Kakamega. These findings highlight the complex trade-offs between maize stover utilization for energy production and its role in maintaining soil health, emphasizing the need for balanced resource management strategies.